Unlocking Green Growth: Investigating Sustainable Finance Instruments For Msmes In Chennai (International Journal of Environmental Sciences, 2025)
The growing urgency of climate change has underscored the need for a green economy, with micro, small, and medium enterprises (MSMEs) playing a vital role. This study examines the adoption and challenges of sustainable finance among 390 MSMEs in Chennai, using a quantitative approach with structured questionnaires. Sustainable finance tools like green bonds and ESG-linked credit lines can support greener practices, yet access and awareness remain low. Only 26% of firms had used such tools, mainly larger manufacturing businesses. Key motivators include regulatory compliance, customer demand, and government incentives, while barriers include lack of awareness, high compliance costs, and complex procedures. Findings show a positive link between sustainable finance use and improved resource efficiency and competitiveness. The study highlights the need for targeted policies, stakeholder collaboration, and simplified access to green finance. Tailored financial products and capacity-building efforts are essential for enabling MSMEs to contribute meaningfully to India’s green transition.